Method for preparing high-length-diameter-ratio and high-purity Si3N4 whisker by adopting Mg as additive through one-step method

By using Mg as an additive in the preparation of silicon nitride whiskers, the MgSiN2 additives are generated in situ, and the problems of uneven distribution of additives and low whisker performance in the prior art are solved, and the preparation of silicon nitride whiskers with high aspect ratio and high purity are achieved, thereby improving the dispersion and yield of whiskers.

CN119800511AActive Publication Date: 2025-04-11NAT UNIV OF DEFENSE TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411994311.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The problems of low length and diameter ratio of silicon nitride whiskers, difficulty in dispersing, and low purity caused by the use of oxide additives in the prior art, and the problems of uneven distribution of additives and raw materials, resulting in reduced whisker conversion and purity.

Method used

A one-step method of preparing high-even-diameter ratio and high-purity Si3N4 whiskers using Mg as an additive is used. MgSiN2 is generated in situ on the surface of Si3N4 particles by molten salt to achieve uniform distribution of additives, and high-even-diameter ratio and high-purity silicon nitride whiskers are obtained through high-temperature sintering treatment.

Benefits of technology

The uniform distribution of additives is achieved, the aspect ratio and purity of silicon nitride whiskers are improved, the residual intergranular phase after cooling is reduced, and the dispersion and yield of whiskers are promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800511A_ABST
    Figure CN119800511A_ABST
Patent Text Reader

Abstract

The invention discloses a one-step method for preparing high-length-diameter-ratio and high-purity Si3N4 whiskers by adopting Mg as an additive, magnesium powder and alpha-Si3N4 powder are adopted as main raw materials, Mg and Si3N4 react in a molten salt system formed by high-temperature melting of metal salt to generate MgSiN2 on the surfaces of Si3N4 particles in situ to serve as a sintering aid, and Si3N4 and MgSiN2 core-shell structure powder is formed. MgSiN2 is further heated to participate in formation of a liquid phase, alpha-Si3N4 in the liquid phase is changed into a beta phase and grows into long rod-shaped crystal whiskers, and MgSiN2 can be decomposed into Si3N4 and gas-phase Mg and N2 at high temperature, so that high purity of the crystal whiskers is guaranteed. According to the method, uniform distribution of the auxiliary agent is realized, the dosage of the auxiliary agent is reduced, and meanwhile, the whisker can be further dispersed by decomposition of MgSiN2, so that the length-diameter ratio and the dispersity of the Si3N4 whisker are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon nitride ceramic whiskers, and in particular relates to a method for preparing high-aspect-ratio high-purity Si3N4 whiskers in a one-step process by using Mg as an additive. Background Art

[0002] Whiskers are a kind of artificially controlled one-dimensional single crystal material. Because of their small size, highly ordered atomic structure, complete crystal structure, few internal defects, and performance indicators close to ideal crystals, they are often introduced as reinforcement phases into ceramic-based, metal-based, and polymer-based material matrices to play the role of reinforcement and toughening. Silicon nitride whiskers have many excellent properties such as high strength, high modulus, high temperature resistance, high thermal conductivity, low density, low expansion, and good chemical stability due to their unique lattice characteristics. They are an ideal reinforcement phase material for composite material systems.

[0003] Now, a whisker preparation method has been developed that directly heats α-Si3N4 at high temperature to cause it to undergo phase change and rearrange its structure to grow into long rod-shaped β-Si3N4 whiskers. In the reaction process, it is generally necessary to add sintering aids to reduce the temperature, gas pressure and other conditions required for the reaction. At the same time, the additives can also improve the performance of the whiskers obtained by sintering. At present, among the additives for sintering β-Si3N4 whiskers, the research on metal oxide additives is the most mature, and there are also many non-oxide additives such as hydrides, fluorides, and nitrides.

[0004] Magnesium silicon nitride, as a non-oxide sintering aid, can effectively reduce the oxygen content in the liquid phase and hinder the formation of lattice oxygen, thereby effectively improving the thermal conductivity and mechanical properties of silicon nitride. It will undergo a decomposition reaction at high temperatures, decomposing into gas and removing it from the sintering system, thereby improving the purity of the product. It also has a certain effect on the dispersion of whiskers, reducing the adhesion of the residual liquid phase to the whiskers after cooling after sintering.

[0005] At present, most methods for preparing silicon nitride whiskers by heat treatment mostly use mechanical mixing methods such as ball milling to mix silicon nitride powder raw materials with sintering aids. This traditional mixing method will result in a certain uneven distribution of additives, and the amount of additives in some raw materials is insufficient, which affects the phase transformation of silicon nitride and the radial growth of whiskers. To solve this problem, more additives need to be added, which will affect the yield and purity of the whiskers. Summary of the invention

[0006] In view of the problems of low aspect ratio, difficulty in dispersion and low purity of whiskers caused by the use of oxide additives in the prior art, as well as the uneven distribution of additives and raw materials, which leads to reduced whisker conversion rate and purity, the present invention provides a method for preparing high aspect ratio and high purity Si3N4 whiskers in a one-step method by using Mg as an additive. Si3N4 powder is used as raw material and magnesium powder is used as an additive. MgSiN2-coated Si3N4 core-shell structure powder is prepared by sintering using a molten salt method, so that uniform distribution of the additive is achieved, and then the temperature is continued to be raised to sinter high aspect ratio and high purity silicon nitride whiskers, and the whisker aspect ratio is 20-40.

[0007] The technical principles of the present invention are as follows:

[0008] 3Mg+Si3N4+N2→3MgSiN2

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing high-aspect ratio high-purity Si3N4 whiskers in one step by using Mg as an additive comprises the following steps:

[0011] (1) mixing silicon nitride powder, magnesium powder and metal salt to obtain a raw material powder;

[0012] The mass ratio of the magnesium powder to silicon nitride is 1:(15-100);

[0013] The mass ratio of the magnesium powder plus silicon nitride powder to the metal salt is 1:(1-3);

[0014] The metal salt is one or more of sodium salt, potassium salt and magnesium salt; wherein the sodium salt is one or two of sodium chloride, sodium bromide and the like, the potassium salt is one or more of potassium fluoride, potassium chloride, potassium bromide and the like, and the magnesium salt is magnesium chloride, and the mixture can be in any proportion;

[0015] The mixing of silicon nitride powder, magnesium powder and metal salt is performed by grinding silicon nitride powder, magnesium powder and alkali metal salt and then mixing them by ball milling at a speed of 300 rpm-400 rpm for 1 h-12 h.

[0016] (2) subjecting the raw material powder obtained in the above step to high-temperature sintering treatment in a nitrogen atmosphere, and after the sintering treatment is completed, cooling to room temperature with the furnace to obtain high-aspect ratio and high-purity Si3N4 whiskers, wherein the whisker aspect ratio is 20-40, and the whisker diameter is uniform, and there is no residual amorphous phase;

[0017] The high-temperature sintering treatment adopts pressureless sintering. The sintering temperature in the first stage is 1000℃-1400℃, and the sintering insulation time is 1h-8h; the sintering temperature in the second stage is 1400℃-1500℃, and the sintering insulation time is 1h-12h; the sintering temperature in the third stage is 1600℃-1800℃, and the sintering insulation time is 1h-8h. The heating rate during the sintering process is 1℃ / min-15℃ / min.

[0018] In the present invention:

[0019] Preferably, in step (1), the mass ratio of magnesium powder to silicon nitride is 1:(15-30).

[0020] Preferably, in step (1), the mass ratio of magnesium powder plus silicon nitride powder to metal salt is 1:(1.5-2.5).

[0021] Preferably, the metal salt in step (1) is one or more of a sodium salt, a potassium salt, and a magnesium salt; wherein the sodium salt is one or two of sodium chloride, sodium bromide, etc., the potassium salt is one or more of potassium fluoride, potassium chloride, potassium bromide, etc., and the magnesium salt is magnesium chloride. The salt system is divided into three types, namely, a monobasic system, a binary system, and a ternary system. The salt type is optional and can be mixed in any proportion.

[0022] Preferably, the ball milling method is used for mixing in step (1), and the rotation speed of the ball milling treatment is 300 rpm-350 rpm and the time is 4 h-12 h.

[0023] Preferably, the pressureless sintering described in step (2) is performed in a nitrogen atmosphere with a pressure ≥ 0.1 MPa, wherein the high N2 pressure during high-temperature sintering can prevent MgSiN2 from decomposing at high temperatures, allowing it to fully play the role of an auxiliary agent.

[0024] Preferably, the temperature of the first stage sintering in step (2) is 1300°C, and the holding time is 2h. Before the first stage sintering process, the salt has melted, a molten salt system is formed, and Mg is dissolved in the molten salt system to achieve uniform dispersion of Mg around the Si3N4 particles. During the sintering process, Mg reacts with Si3N4 to generate MgSiN2 in situ on the surface of Si3N4. Therefore, the process is carried out in a molten salt system, the distribution of Mg is more uniform, the generation of MgSiN2 is also more uniform, and the uniform distribution of the additive can be better achieved.

[0025] Preferably, the temperature of the second stage sintering in step (2) is 1400°C, and the holding time is 4 hours. The holding temperature of this stage needs to be higher than the boiling point of the metal salt to ensure that after the MgSiN2 formation reaction is completed, the molten salt can be gasified and removed from the raw material system by heating to avoid affecting the subsequent Si3N4 phase transformation and whisker growth process.

[0026] Preferably, the temperature of the third stage sintering in step (2) is 1650℃-1750℃, the holding time is 1h-4h, the optimal heat treatment process is 1700℃ holding for 2h, the heating rate during the sintering process is 5℃ / min-15℃ / min, and after the three stages of sintering are completed, the sample is cooled to room temperature with the furnace.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. Compared with the conventional process of using metal oxide sintering aids to sinter silicon nitride whiskers, there is a certain amount of intergranular phase in the final product after the metal-containing liquid phase is cooled, which will adhere to the surface of the whiskers and cause adhesion to the whiskers. An additional process is required to remove it, affecting the quality of the whiskers. The method of preparing high-aspect ratio and high-purity Si3N4 whiskers in one step using Mg as an additive described in the present invention can, due to the presence of the reaction 3MgSiN2(s)→3Mg(g)+Si3N4(s)+N2(g), make the sintering aid MgSiN2 decompose at high temperature after playing the role of an auxiliary agent by regulating the temperature and the pressure of the nitrogen atmosphere, remove the silicon nitride system, reduce the amount of intergranular phase remaining after cooling, slow down the adhesion of the intergranular phase to the whiskers, and at the same time, the decomposed gas products have a certain promoting effect on the dispersion of the whiskers.

[0029] 2. The present invention discloses a method for preparing high-aspect-ratio and high-purity Si3N4 whiskers in one step by using Mg as an additive. MgSiN2 is generated in situ on the surface of Si3N4 particles by a molten salt method, so that the distribution of the additive is more uniform and the role of the additive is more fully exerted, thereby indirectly reducing the amount of the additive and improving the yield and purity of the whiskers. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0031] Figure 1 is an XRD diagram of the Si3N4 whisker prepared by a one-step method using Mg as an additive in Example 3 of the present invention and the Si3N4 whisker prepared by a ball milling method using Y2O3 as a sintering aid in Comparative Example 1;

[0032] Figure 2 1-5 and 1-2 of the present invention are SEM images of whiskers prepared in Examples 1-5 and Comparative Examples 1-2 (wherein (a)-(e) correspond to Examples 1-5, respectively, and (f)-(g) correspond to Comparative Examples 1-2);

[0033] Figure 3 is a SEM image of the whiskers obtained in Example 3. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0035] In this specific implementation mode:

[0036] The silicon nitride powder has an average particle size of 0.5 μm, a purity of >99.5%, an α-phase content of >95wt%, and an oxygen content of 1.35%;

[0037] The purity of the magnesium powder is ≥99.0wt%, and the particle size of the magnesium powder is 10-150μm;

[0038] The purity of the potassium chloride is ≥99.5wt%, and the particle size of the sodium chloride is ≤0.1mm;

[0039] The purity of the sodium chloride is ≥99.5wt%, and the particle size of the sodium chloride is ≤0.1mm.

[0040] The present invention uses Mg as an additive to prepare a high-aspect ratio high-purity Si3N4 whisker in a one-step method, such as Figure 1 as shown in .

[0041] Embodiment 1:

[0042] A method for preparing high-aspect ratio and high-purity Si3N4 whiskers in a one-step process using Mg as an additive, the specific steps are:

[0043] Step 1, weigh 46.875 g of silicon nitride particles and 3.125 g of magnesium powder, add 50 g of sodium chloride particles, and ball mill at 300 rpm for 4 h to obtain a mixed raw material;

[0044] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1300°C and keep it for 2 hours, then heat to 1400°C and keep it for 4 hours, and finally heat to 1700°C and keep it for 2 hours, with a heating rate of 10°C / min; after sintering, cool to room temperature with the furnace.

[0045] The whisker samples finally obtained had an average length of 7.810 μm, an average diameter of 0.282 μm, and an average value of the calculated aspect ratio of 28.221.

[0046] Embodiment 2:

[0047] A method for preparing high-aspect ratio and high-purity Si3N4 whiskers in a one-step process using Mg as an additive, the specific steps are:

[0048] Step 1, weigh 48g of silicon nitride particles and 2g of magnesium powder, add 50g of sodium chloride particles and 50g of potassium chloride particles, and ball mill at 300rpm for 8h to obtain a mixed raw material;

[0049] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1300°C and keep it for 2 hours, then heat to 1400°C and keep it for 4 hours, and finally heat to 1750°C and keep it for 2 hours, with a heating rate of 10°C / min; after sintering, cool to room temperature with the furnace.

[0050] The whisker samples finally obtained had an average length of 9.050 μm, an average diameter of 0.350 μm, and an average value of the calculated aspect ratio of 26.976.

[0051] Embodiment 3:

[0052] A method for preparing high-aspect ratio and high-purity Si3N4 whiskers in a one-step process using Mg as an additive, the specific steps are:

[0053] Step 1, weigh 46.875 g of silicon nitride particles and 3.125 g of magnesium powder, add 50 g of sodium chloride particles and 50 g of potassium chloride particles, and ball mill at 400 rpm for 8 h to obtain a mixed raw material;

[0054] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1300°C and keep it for 2 hours, then heat to 1400°C and keep it for 4 hours, and finally heat to 1700°C and keep it for 2 hours, with a heating rate of 10°C / min; after sintering, cool to room temperature with the furnace.

[0055] The whisker samples finally obtained had an average length of 9.147 μm, an average diameter of 0.265 μm, and an average value of the calculated aspect ratio of 35.223.

[0056] Figure 1 is an XRD diagram of the Si3N4 whisker prepared by a one-step method using Mg as an additive in Example 3 and the Si3N4 whisker prepared by a ball milling method using Y2O3 as a sintering aid in Comparative Example 1;

[0057] Figure 3 is a SEM image of the whiskers obtained in Example 3.

[0058] Embodiment 4:

[0059] A method for preparing high-aspect ratio and high-purity Si3N4 whiskers in a one-step process using Mg as an additive, the specific steps are:

[0060] Step 1, weigh 49 g of silicon nitride particles and 1 g of magnesium powder, add 50 g of sodium chloride particles and 50 g of potassium chloride particles, and ball mill at 400 rpm for 12 h to obtain a mixed raw material;

[0061] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1300°C and keep it for 2 hours, then heat to 1400°C and keep it for 4 hours, and finally heat to 1650°C and keep it for 2 hours, with a heating rate of 10°C / min; after sintering, cool to room temperature with the furnace.

[0062] The average length of the whisker samples finally obtained was 7.518 μm, the average diameter was 0.303 μm, and the average value of the calculated aspect ratio was 24.917.

[0063] Embodiment 5:

[0064] A method for preparing high-aspect ratio and high-purity Si3N4 whiskers in a one-step process using Mg as an additive, the specific steps are:

[0065] Step 1, weigh 49 g of silicon nitride particles and 1 g of magnesium powder, add 50 g of sodium chloride particles and 50 g of potassium chloride particles, and ball mill at 400 rpm for 12 h to obtain a mixed raw material;

[0066] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1300°C and keep warm for 2 hours, then heat to 1400°C and keep warm for 4 hours, and finally heat to 1700°C and keep warm for 4 hours, with a heating rate of 10°C / min; after sintering, cool to room temperature with the furnace.

[0067] The average length of the whisker samples finally obtained was 9.421 μm, the average diameter was 0.379 μm, and the average value of the calculated aspect ratio was 25.440.

[0068] Figure 2 These are SEM images of the whiskers prepared in Examples 1-5 and Comparative Examples 1-2 (where (a)-(e) correspond to Examples 1-5, respectively, and (f)-(g) correspond to Comparative Examples 1-2).

[0069] Comparative Example 1:

[0070] The specific steps are:

[0071] Step 1: Weigh 47 g of silicon nitride particles, add 3 g of yttrium oxide particles, add 100 g of anhydrous ethanol, and ball mill for 12 hours to obtain a mixed slurry, and dry the mixed slurry in an oven at 60° C. for 12 hours to obtain a mixed powder;

[0072] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1700°C at a heating rate of 10°C / min, and keep warm for 2 hours; after sintering, cool to room temperature with the furnace.

[0073] The difference between Comparative Example 1 and the embodiment is that Comparative Example 1 uses directly added Y2O3 as a sintering aid, while the aid in the embodiment is MgSiN2 generated by the in-situ reaction of Mg and Si3N4, which is a non-oxide sintering aid. The oxygen content in the system is lower, and the formed liquid phase viscosity is higher, which is more conducive to the formation of a local liquid phase and promotes the independent growth of a single whisker. Moreover, MgSiN2 can be removed from the system after the sintering action is completed, thereby improving the purity of the sample.

[0074] The average length of the whisker samples finally obtained was 6.871 μm, the average diameter was 0.395 μm, and the average value of the calculated aspect ratio was 17.468.

[0075] Comparative Example 2:

[0076] The specific steps are:

[0077] Step 1: Weigh 47 g of silicon nitride particles, add 3 g of magnesium silicon nitride particles, add 100 g of anhydrous ethanol, and ball mill for 12 hours to obtain a mixed slurry, and dry the mixed slurry in an oven at 60° C. for 12 hours to obtain a mixed powder;

[0078] Step 2: Sinter the obtained raw materials in a nitrogen atmosphere, heat to 1700°C at a heating rate of 10°C / min, and keep warm for 2 hours; after sintering, cool to room temperature with the furnace.

[0079] The difference between Comparative Example 2 and the embodiment is that Comparative Example 2 directly adds MgSiN2 as a sintering aid, while the aid in the embodiment is MgSiN2 generated by the in-situ reaction of Mg and Si3N4. Compared with directly adding aids, in-situ generated aids can better achieve uniform distribution of the aids, more fully realize the effect of the aids, indirectly reduce the amount of aids used, and improve the yield and purity of the sample.

[0080] The average length of the whisker samples finally obtained was 8.542 μm, the average diameter was 0.457 μm, and the average value of the calculated aspect ratio was 19.122.

[0081] Results and Discussion:

[0082] 1. In the present invention, an X-ray diffractometer (Shimadzu XRD-6100, Japan) was used to test the phase composition of the whisker samples obtained in Example 3 and Comparative Example 1. The results are shown in Figure 1 ;

[0083] It can be seen that in the final product of Comparative Example 1 using Y2O3 as a sintering aid, a certain proportion of Y-containing glass phase will appear. After refined calculation, it can be obtained that the mass ratio of the Y-containing glass phase in the sample reaches 13.7wt%, which has an adverse effect on the yield and dispersion of whiskers. In the final product of Example 3 using MgSiN2 as a sintering aid, there is only β-Si3N4 phase, and no Mg-containing glass phase remains. The whisker product has a higher purity and is easier to disperse.

[0084] 2. In the present invention, a scanning electron microscope (Hitachi Regulus 8100) was used to observe the microscopic morphology and whisker quality of the whisker samples obtained in the embodiment and the comparative example. Figure 2 ;

[0085] It can be seen that when the mass ratio of magnesium to silicon nitride in the raw material is 1:(15-100), the amount of additives generated is sufficient to meet the whisker growth requirements. Too much magnesium addition will reduce the whisker yield and cause unnecessary waste. Too little magnesium addition will result in insufficient additives to support the entire process of phase change and whisker growth. The mass ratio of magnesium powder to silicon nitride is 1:(15-30) for better results, and the mass ratio of magnesium powder to silicon nitride is 1:15 for the best results. In the process of in-situ growth of MgSiN2, the binary molten salt system has better Mg dispersion than the monolithic one. When the mass ratio of magnesium powder plus silicon nitride powder to salt is 1:2 or above, Mg has better dissolution and dispersion effects in the molten salt system. Increasing the sintering temperature and extending the holding time will increase the average diameter of the whiskers.

[0086] From the analysis of Examples 1-5 and Comparative Example 1, it can be seen that the surface of the obtained whiskers is smoother and purer when MgSiN2 is used as a sintering aid, while in the sample using Y2O3 as a sintering aid, there are many residual glass phase particles, which adhere to the whiskers and are not conducive to the dispersion of the whiskers;

[0087] From the analysis of Examples 1-5 and Comparative Example 2, it can be seen that by using the molten salt method to in-situ generate MgSiN2, the distribution of the additive is more uniform, and a similar whisker growth effect can be achieved with a smaller amount of additive. In addition, the magnesium silicon nitride additive is generated on the surface of the silicon nitride particles, which can directionally generate a liquid phase and promote the directional growth of whiskers. This reduces the cross-growth of whiskers to a certain extent, making the dispersion of whiskers easier.

[0088] 3. In the present invention, Nano measurer software is used to measure the length and diameter of the whiskers in the SEM image. The final whisker average diameter, average length and average aspect ratio results are shown at the end of each embodiment and comparative example. By comparing the measurement data and SEM images of the whisker samples obtained in all experiments, it can be found that:

[0089] ① It can be found from the data of Example 1 and Example 3 that Example 1 uses a monovalent molten salt, and Example 3 uses a binary molten salt. The results show that the use of a binary molten salt can provide a more balanced molten salt system for shell growth, and the higher the salt dosage, the better the shell growth effect, which is more conducive to whisker development;

[0090] ② By comparing the data of Examples 1-5, it can be found that the higher the heat treatment temperature and the holding time, the larger the diameter of the grown whiskers, which will affect the aspect ratio of the whiskers to a certain extent. The optimal heat treatment process is 1700°C for 2h;

[0091] ③ By comparing Examples 3-5, it can be found that when the mass ratio of magnesium to silicon nitride in the raw material is 1:15, the effect of whisker growth is optimal;

[0092] ④ By comparing Example 3 with Comparative Examples 1-2, it can be found that the aspect ratio of the whiskers prepared by the preparation process proposed by the present invention is better than that of the preparation process of directly adding a sintering aid.

[0093] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing high-aspect ratio high-purity Si3N4 whiskers in one step using Mg as an additive, characterized in that: The following steps are involved: (1) mixing silicon nitride powder, magnesium powder and metal salt to obtain a raw material powder; The mass ratio of the magnesium powder to silicon nitride is 1:(15-100); The mass ratio of the magnesium powder plus silicon nitride powder to the metal salt is 1:(1-3); The metal salt is one or more of sodium salt, potassium salt and magnesium salt; wherein the sodium salt is one or two of sodium chloride, sodium bromide and the like, the potassium salt is one or more of potassium fluoride, potassium chloride, potassium bromide and the like, and the magnesium salt is magnesium chloride, and the mixture can be in any proportion; The mixing of silicon nitride powder, magnesium powder and metal salt is performed by grinding silicon nitride powder, magnesium powder and alkali metal salt and then mixing them by ball milling at a speed of 300 rpm-400 rpm for 1 h-12 h. (2) subjecting the raw material powder obtained in the above step to high-temperature sintering treatment in a nitrogen atmosphere, and after the sintering treatment is completed, cooling to room temperature with the furnace to obtain high-aspect ratio and high-purity Si3N4 whiskers, wherein the whisker aspect ratio is 20-40 and there is no residual amorphous phase; The high-temperature sintering treatment adopts pressureless sintering. The sintering temperature in the first stage is 1000℃-1400℃, and the sintering insulation time is 1h-8h; the sintering temperature in the second stage is 1400℃-1500℃, and the sintering insulation time is 1h-12h; the sintering temperature in the third stage is 1600℃-1800℃, and the sintering insulation time is 1h-8h. The heating rate during the sintering process is 1℃ / min-15℃ / min.

2. The method for preparing high-purity Si3N4 whiskers with high aspect ratio by one-step method using Mg as an additive according to claim 1, characterized in that: In step (1), the mass ratio of magnesium powder to silicon nitride is 1:(15-30).

3. The method for preparing high-purity Si3N4 whiskers with high aspect ratio by one-step method using Mg as an additive according to claim 1, characterized in that: In step (1), the mass ratio of magnesium powder plus silicon nitride powder to metal salt is 1:(1.5-2.5).

4. The method for preparing high-aspect ratio high-purity Si3N4 whiskers by one-step method using Mg as an additive according to claim 1, characterized in that: The metal salt in step (1) is one or more of a sodium salt, a potassium salt, and a magnesium salt; wherein the sodium salt is one or two of sodium chloride, sodium bromide, etc., the potassium salt is one or more of potassium fluoride, potassium chloride, potassium bromide, etc., and the magnesium salt is magnesium chloride. The salt system is divided into three types, namely, a monobasic system, a binary system, and a ternary system. The salt type is optional and can be mixed in any proportion.

5. The method for preparing high-aspect ratio high-purity Si3N4 whiskers by one-step method using Mg as an additive according to claim 1, characterized in that: The ball milling method described in step (1) is used for mixing at a rotation speed of 300 rpm-350 rpm for 4 h-12 h.

6. The method for preparing high-purity Si3N4 whiskers with high aspect ratio by one-step method using Mg as an additive according to claim 1, characterized in that: The pressureless sintering described in step (2) is carried out in a nitrogen atmosphere with a pressure ≥ 0.1 MPa.

7. The method for preparing high-aspect ratio high-purity Si3N4 whiskers by one-step method using Mg as an additive according to claim 1, characterized in that: The first stage sintering temperature in step (2) is 1300° C. and the holding time is 2 h.

8. The method for preparing high-aspect ratio high-purity Si3N4 whiskers by one-step method using Mg as an additive according to claim 1, characterized in that: The temperature of the second stage sintering in step (2) is 1400° C. and the holding time is 4 hours.

9. The method for preparing high-purity Si3N4 whiskers with high aspect ratio by one-step method using Mg as an additive according to claim 1, characterized in that: The temperature of the third stage sintering in step (2) is 1700° C. and the holding time is 2 h.

Citation Information

Patent Citations

  • Method for preparing high-thermal-conductivity and high-strength silicon nitride ceramic by adopting core-shell structure Si3N4-coated MgSiN2 powder

    CN117550901A

  • Preparation for combustion synthesis of beta-silicon nitride stick grain with magnesium silicon nitride as growth aid

    CN1569742A

  • Method for preparing silicon nitride powder by metal reduction

    WO2021008089A1